SISTEM INTELIJEN BISNIS GLOBAL UNTUK PERENCANAAN E-COMMERCE - Budi Susilo (STMIK PONTIANAK, 2011)
Abstracts: The first step to reach the E-commerce is to understand the environments in which trading would take place. Business Intelligence is an activity of gathering information about the environmental elements that interact with the company. E-commerce failure to achieve planned goals, because the understanding of the environmental conditions of trade faced by the company is not in accordance with E-commerce applications are implemented. This is due to the information collected can not provide a clear picture of environmental conditions. This study aims to describe the fields of information and categories that can be used as a starting point to describe the environmental conditions that affect the company globally. Global Business Intelligence System is used as a general framework, which can be developed according to specific company needs and objectives. In general, the system consists of six fields of information and 31 categories. The process of collecting information in this system using a Modus Scanning that has the characteristics of active and focused on the desired categories. Each information field with the categories that have described the different influences, both as a driving force, the power resistor, and by providing pressure to the company's business. Differences influence of environmental conditions provides an explanation of the level of preparedness organizations in the application of E-commerce, as a business strategy to gain competitive advantage. Keywords: Business Intelligence, Global Business Intelligence Systems, E-commerce, Modus Scanning